Gothic science fiction 1980-2010 - Wasson, Sara; Alder, Emily (Liverpool science fiction texts and studies ;, 2011)
These essays explore questions of genre, medical science gender, biopower and capitalism, demonstrating the ways in which Gothic science fiction texts stage contemporary concerns around power, anxiety, resistance and capital.